Challenges for junior high school mathematics teachers in preparing to implement the independent curriculum - Suripah, Suripah; Pratiwi, Aisha Widya; Agustyani, Anggit Reviana Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2023)
This research aims to describe the challenges of junior high school mathematics teachers in Pekanbaru in preparing to implement the independent curriculum. This type of research is a mixture of quantitative and qualitative research. The subjects of this research were 10 teachers from 5 schools in Pekanbaru. Data was collected using interviews, FGD, and questionnaires. Based on the results of data analysis, the challenges for mathematics teachers in preparing an independent curriculum are as follows. First, training and socialization have not been able to provide complete understanding for teachers in preparing the Independent Curriculum. Second, teachers try to overcome difficulties in planning learning in the Independent Curriculum. Third, the implementation of learning is not appropriate and the facilities and infrastructure at school are not yet supportive, coupled with differences in the cognitive background of students. Fourth, teachers need to improve their understanding completely regarding the system for assessing and reporting learning outcomes in the Independent Curriculum. Then, if we trace it based on the questionnaire, we can conclude that the preparation for implementing the Independent Curriculum by junior high school mathematics teachers in Pekanbaru, even though they are still experiencing various challenges, is in the Good category (70% < score < 84%.), with details, 5 teachers are in the adequate category while 5 people are in the Good category.